Effects of long term device-guided slow breathing on sympathetic nervous activity in hypertensive patients: a randomized open-label clinical trial - Silvana de Barros; Giovanio Vieira da Silva; Josiane Lima de Gusmão; Tatiana Goveia de Araújo; Dinoélia Rosa de Souza; Crivaldo Gomes Cardoso; Bruna Oneda; Décio Mion (Blood Pressure, 2017)
Purpose: Device-guided slow breathing (DGB) is indicated as nonpharmacological treatment for hypertension. The sympathetic nerve activity (SNA) reduction may be one of the mechanisms involved in blood pressure (BP) decrease. The aim of this study is to evaluate the long-term use of DGB in BP and SNA. Subjects and methods: Hypertensive patients were randomized to listen music (Control Group–CG) or DGB (aim to reduce respiratory rate to less than 10 breaths/minute during 15 minutes/day for 8 weeks). Before and after intervention ambulatory blood pressure monitoring (ABPM), catecholamines and muscle sympathetic nerve activity (MSNA) by microneurography were performed. Results: 17 volunteers in the DGB and 15 in the CG completed the study. There was no change in office BP before and after intervention in both groups. There was a reduction in systolic and diastolic BP in the awake period by ABPM only in the CG (131 ± 10/92 ± 9 vs 128 ± 10/88 ± 8mmHg, p < 0.05). In relation to SNA, no difference in catecholamines was observed. In the volunteers who had a microneurography record, there was no change the MSNA (bursts/minute): DGB (17(15–28) vs 19(13–22), p = 0.08) and CG (22(17–23) vs 22(18–24), p = 0.52). Conclusion: Long-term DGB did not reduce BP, catecholamines levels or MSNA in hypertensive patients. ClinicalTrials.gov identifier: NCT01390727